2020
DOI: 10.21203/rs.3.rs-17129/v6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Y chromosome markers in the eastern three-lined skink (Bassiana duperreyi) using in silico whole genome subtraction.

Abstract: Background: Homologous sex chromosomes can differentiate over time because recombination is suppressed in the region of the sex determining locus, leading to the accumulation of repeats, progressive loss of genes that lack differential influence on the sexes and sequence divergence on the hemizygous homolog. Divergence in the non-recombining regions leads to the accumulation of Y or W specific sequence useful for developing sex-linked markers. Here we use in silico whole-genome subtraction to identify putative… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…They have broadly parapatric distributions (Figure 1). The south‐eastern highland and alpine taxon is of particular interest, because it has a system of sex determination that involves both differentiated sex chromosomes and sex reversal of the XX genotype to a male phenotype at a frequency that varies predictably with elevation and nest temperatures (Dissanayake et al, 2020, 2021; Dissanayake et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…They have broadly parapatric distributions (Figure 1). The south‐eastern highland and alpine taxon is of particular interest, because it has a system of sex determination that involves both differentiated sex chromosomes and sex reversal of the XX genotype to a male phenotype at a frequency that varies predictably with elevation and nest temperatures (Dissanayake et al, 2020, 2021; Dissanayake et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in B. duperreyi, heteromorphic sex chromosomes were first detected using cytogenetic approaches [Shine et al, 2002] and then sex reversal was first demonstrated using PCR targeting a sequence unique to the Y chromosome [Radder et al, 2008], which was later refined using similar methods [Quinn et al, 2009]. New markers for this species have also been identified using an in silico whole genome subtraction approach [Dissanayake et al, 2020].…”
Section: Detection Of Sex Reversalmentioning
confidence: 99%
“…Identifying and confirming genotypic sex in reptiles can be challenging, requiring considerable time and resources to develop reliable assays. Homomorphic sex chromosomes are common in reptiles, necessitating the use of advanced cytological techniques [Ezaz et al, 2005] or sequencing technologies to identify sex-specific sequences [Sankovic et al, 2006;Chen et al, 2012;Traut et al, 2013;Palmer et al, 2019;Cornejo-Paramo et al, 2020;Dissanayake et al, 2020]. There is also limited understanding as to the individual-and population-level consequences of sex reversal in the wild, particularly under changing climatic regimes [Bókony et al, 2017;Schwanz et al, 2020].…”
mentioning
confidence: 99%